Pharmacokinetic profile of sildenafil citrate in healthy Middle Eastern Males: Comparison with other ethnicities - Abdulrahman Alwhaibi; Sary Alsanea; Ziyad Alrabiah; Fars K. Alanazi; Badraddin M. Al-Hadiya; Hisham S. Abou-Auda (Elsevier, 2021)
Aim: 1) To investigate the pharmacokinetic profile of sildenafil citrate in Middle Eastern males and, 2) To highlight the impact of ethnicity on its pharmacokinetics parameters through comparing Middle Eastern data to the data estimated from different ethnic groups. Method: The study was conducted on 24 Middle Eastern healthy male volunteers. Pharmacokinetic data including Cmax, Tmax, t1/2, AUC0-t, AUC0-∞ were estimated from blood samples collected at several time points within 24 h post-administration of a single 100-mg tablet of sildenafil citrate (Viagra®). Pharmacokinetic data of sildenafil generic 100-mg tablet (product B) was determined in the volunteers using the same analytical method. Pharmacokinetic data of other studies published on different ethnicities were obtained and compared to our Viagra®-related data. Results: Analysis of Middle Eastern data (mean ± SD) revealed Cmax = 398.9 ± 107.7 ng/ml; Tmax = 1.84 ± 0.22 h; t1/2 = 2.66 ± 0.97 h; AUC0-24 = 1475 ± 515.3 ng.h/ml; AUC0-∞ = 1556 ± 567.58 ng.h/ml. There was no significant difference between Viagra® and product B, confirming the bioequivalence of the two preparation as well as the reliability of utilized analytical method. Data comparisons between Middle Eastern and other ethnicities indicated that Iranian, Mexican, and Thai would potentially have twice the effect observed in Arabs and Caucasians, considering the same prescribed drug formulation and dose. Conclusion: There is a considerable difference in the pharmacokinetic profile of sildenafil citrate between Middle Eastern and other ethnic groups. Ethnicity may predispose individuals to unwanted prolonged activity of sildenafil and adverse events. Thus, it should be taken in consideration by clinicians when recommending sildenafil dose.